2015
DOI: 10.5604/15093492.1193032
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Lumbopelvic and Hip Movement Patterns During Passive Hip External Rotation in Two Groups of Low Back Pain Patients with and without Rotational Demand Activities

Abstract: 1. A greater lumbopelvic rotation ROM during the PHER existed in LBP patients who regularly participated in RDA. 2. Different groups of patients with LBP who engage in different specific activities may have a specific lumbopelvic movement pattern impairment. Therefore, each group of LBP patients in regard to their specific activities may need a different, specific plan of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Regarding the hip joint, the reduced hip extension in patients with LBP and compensatory lumbar spine rotation during hip movements are consistent in the literature [ 31 , 32 , 33 , 34 ]. Thus, this hip extension limitation is directly associated with greater hip extension asymmetry, pain intensity, and disability in general LBP populations.…”
Section: Discussionsupporting
confidence: 88%
“…Regarding the hip joint, the reduced hip extension in patients with LBP and compensatory lumbar spine rotation during hip movements are consistent in the literature [ 31 , 32 , 33 , 34 ]. Thus, this hip extension limitation is directly associated with greater hip extension asymmetry, pain intensity, and disability in general LBP populations.…”
Section: Discussionsupporting
confidence: 88%
“…Patients with nonspecific chronic low back pain exhibited less hip extension mobility than that in healthy people. In addition, compensatory rotation of the lumbar spine occurred during hip movement [ 21 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 , 2 For example, people who regularly participate in rotational demand activities have increased lumbopelvic rotation compared to people who do not participate in rotational demand activities. 16 , 17 Several studies have found that the repetition of movements associated with various sports leads to adaptations in different tissues including bone, joint and its surrounding tissues and muscles. 4 , 5 , 6 , 7…”
Section: Movement System Impairments: Inducers and Modifiersmentioning
confidence: 99%